Remote sensing of suspended sediment in high turbid estuary from sentinel-3A/OLCI: A case study of Hangzhou Bay - Yu, Zhifeng; Wang, Jingwen; Li, Yuan; Shum, CK; Wang, Ben; He, Xianqiang; Xu, Huiyan; Xu, Yuzhuang; Zhou, Bin (Frontiers in Marine Science, 2022)
The suspended sediment in water, infers water quality, directly reflects optical properties such as water transparency, turbidity, and water color. Thus, these physical properties provide a viable basis to rigorously invert for suspended sediment concentration (SSC) using satellite remote sensing measurements of water color in estuarine shores. The contemporary Ocean and Land Color Instrument (OLCI) on Sentinel-3A, provides more waveband options for remote sensing of water color and an opportunity for inversion of suspended sediment in estuarine coast. Yet, accurate retrieval of SSC in high turbid waters from OLCI is still challenge due to the high uncertainty of atmospheric correction. Here, we use OLCI images to measure water quality in Hangzhou Bay estuarine, and construct an inverse model of SSC, and cross-validated using Geostationary Ocean Color Imager (GOCI) data. The study shows that: (1) The atmospheric correction algorithm based on UV spectra (UVAC) can achieve better results for both OLCI and GOCI data, and the overall correction accuracy for OLCI is higher than that for GOCI data; (2) The multi-band index model constructed by using Rrs(Oa16)/Rrs(Oa5) of OLCI data has high inversion accuracy and model stability, with R2 is 0.96, MRE is 17.52%, and RMSE is 69.10 mg/L; (3) The spatial distribution of SSC in the study area is very complex, mainly showing that the SCC in the top of the bay is larger than the mouth of the bay, and the south shore is larger than the north shore; (4) The distribution of SSC obtained from inverting OLCI and GOCI data in general is consistent, with the OLCI SSC estimates with higher accuracy than when GOCI data were used, and the numerical difference between the two inversion results is more obvious in the ocean with high SSC; and (5) With appropriate atmospheric corrections and inversion models, OLCI data can be used to invert for improved SSC observables in the Hangzhou Bay. We conclude that the SSC inversion models proposed here provide a reference method in general for retrieval of this important water color observable in coastal estuarine.